The Persistence of Technology : Histories of Repair, Reuse and Disposal - Krebs, Stefan; Weber, Heike (2021)
Repair, reuse and disposal are closely interlinked phenomena related to the service lives and persistence of technologies. When technical artefacts become old and worn out, decisions have to be taken: is it necessary, worthwhile or even possible to maintain and repair, reuse or dismantle them - or must they be discarded? These decisions depend on factors such as the availability of second-hand markets, repair infrastructures and dismantling or disposal facilities. In telling the stories of China's power grid, Canadian telephones, German automobiles and India's shipbreaking business, among others, the contributions in this volume highlight the persistence of technologies and show that maintenance and repair are not obsolete in modern industries and consumer societies.